Politeness Strategy and Progressive Education Value in The Novel Man and His Storms - Kasanah, Latifah Nurul; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Objective: This study aims to describe the forms of politeness strategies contained in the novel Manusia dan Badainya and to describe the progressive education values contained therein. Methodology: The method used in this research is a descriptive qualitative method with the results in the form of writing. The object studied is the novel Manusia dan Badainya. The data collection technique used is the simak-catat technique. Data analysis techniques include data reduction, presentation, and conclusion. Results: The results of this study indicate that there are 2 forms of politeness strategies which include positive politeness strategies and negative politeness strategies, and 1 progressive education value contained in the novel. The form of politeness strategies in the novel Manusia dan Badainya includes 5 positive politeness strategies and 2 forms of negative politeness strategies. Application/Originality/Value: The novelist writes that the value of progressive education is indirectly contained in the novel Manusia dan Badainya.